Auditor Performance and Public Trust: Towards Higher Accountability in the Era of Technology 4.0 - Firmansyah, Firmansyah; Pardosi, Harta; Putri, Jennifer Olivia Annisa (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study to examine auditor performance in the context of its relationship with the level of public trust, focusing on efforts towards higher accountability in audit practicesThis research involves surveys and data analysis to identify factors that influence the level of public trust in auditors. The results showed that auditor independence, integrity, and professional ethics play an important role in building public trust. In addition, effective communication from auditors to stakeholders is also an important factor in increasing public trust. These findings underscore the importance of transparent and comprehensive auditing practices in creating a more accountable business environment. This research provides valuable insights into the role of auditors in maintaining the integrity of financial markets and demonstrates the importance of cooperation between regulators, the audit profession, and companies in achieving higher accountability. This study contributes to that direction by identifying concrete steps to improve auditor performance and strengthen public confidence in audit practices.